IN VITRO MICRO PROPAGATION OF ORNAMENTAL AND MEDICINAL PLANTS FRITILLARIA IMPERIALIS AND F. PERSICA - Özcan, S.; Gürlek, D.; Çöçü, S.; Uranbey, S.; İpek, A.; Sancak, C.; Arslan, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Fritillaria imperialis and F. persica belonging to Liliaceae family are important ornamental plants because of their attractive and large flowers. Bulbs of Fritillaria species have also been used as herbal remedies in Turkish, Japanese, Pakistani and south-east Asian folk medicines for centuries. However, F. imperialis and F. persica species are endangered species of Turkey and threatened by extinction. The natural propagation rate of most geophytes including F. imperialis and F. persica is relatively low, which often inhibits the large-scale cultivation of these plants. For in vitro micro propagation of these species, many explants including bulb scales and immature embryos were cultured on media containing various combinations of auxins and cytokinins using different culture protocols. Prolific shoot regeneration and bulblet formation was observed from immature embryo explants after one year of culture initiation. Regenerated bulblets were rooted and then transplanted to a potting mixture.